Exploring The Translation of Web Content in The Website - Fitria, Tira Nur (SALIENCE: English Language, Literature, and Education Journal, 2025)
This research explores the translation of a website (web page). This research is library research. As the internet expands in non-English-speaking countries, multilingual websites have become essential for businesses and accessibility. Translating websites into English enhances global reach but presents challenges in technical, content, and linguistic aspects. Technical issues include file formats and encoding, while content considerations involve text, images, and symbols. Linguistically, style, meaning, and idioms require careful handling. Website translation methods include manual and machine translation. Manual translation ensures accuracy, requiring expertise, contextual understanding, and cultural sensitivity. Machine translation, using AI, offers speed, cost-effectiveness, and consistency but may lack nuance and context. Browsers like Google Chrome, Mozilla Firefox, and Microsoft Edge provide built-in translation features, while extensions further enhance accessibility. However, machine translation can negatively impact SEO rankings and fail to consider reader-specific vocabulary. Moreover, translation influences website design and user experience (UX), affecting layout, menus, and usability. Translators must balance linguistic accuracy with usability, ensuring readability without compromising design. Ultimately, effective website translation requires careful planning to maintain accessibility, accuracy, and functionality. The implications of this research indicate the need for a more holistic approach to translating websites, taking into account readability, user experience, and cultural fit. Translators must understand the target audience well and adapt content to suit the local context while maintaining global communication goals.